Atrial Fibrillation One of Hidden Causes of Subclinical Stroke: Case-Control Study (Medico Legal Update, 2021)
Background: Silent cerebral infarction is frequently encountered on various imaging modalities of brain inindividuals with atrial fibrillation, its exact relation with atrial fibrillation is still debated.Objectives: The study was carried out to estimate the link between silent cerebral infarcts with atrialfibrillation, both paroxysmal and persistent types.Materials and Method. A random sample of 150 were included in the study, 100 with atrial fibrillation 50case with paroxysmal, 50 case with persistent type, and 50 control, for both cases and control a questionnairewas constructed, physical examination, neurological examination, and magnetic resonance imaging weredone.Results: Mean age was 64.6667. Of the total sample there was 96 males and 54 females. 89 individual of thetotal sample had silent cerebral lesion while 61 had no lesion. Of those who had lesions, 38 individuals hadparoxysmal atrial fibrillation, 41 had persistent atrial fibrillation, and only 10 individuals belong to controlgroup. There was high statistically significant difference between group of cases with atrial fibrillation andgroup of control in sinus rhythm where p value is 0.0001.Conclusion: Both paroxysmal and persistent atrial fibrillation is associated with heightened hazard of silentcerebral infarctions.